Austrian Linkages to the European Economy and the Transmission Mechanisms of Economic Crisis - Joseph Francois; Mario Holzner; Olga Pindyuk (FIW - Research Centre International Economics, 2011)
Like most of the global economy, Austria suffered from recession in 2008-2009. In this paper we deconstruct the pattern of recession, and the transmission of the global recession to Austria's economy. We provide a new a new breakdown of the value added in Austrian exports, tracing both upstream and downstream linkages and their role in the recession. We also employ a multi-region computable general equilibrium (CGE) model, focused on Austria and its major trading partners. We estimate the combined impacts of the crisis, as implemented through stylized shocks to investment and household demand across major trading partners. These are based on the actual global demand shocks that occurred in 2008-2009. As we are focused on recession, we work with a short-run version of the model, where labor markers are modeled with unemployment and sticky wages, and where industry structure (number of varieties and allocation of capital stock across industries) is fixed. We introduce demand shocks (changes) to global investment demand calibrated from actual investment demand changes during the recession. We also calibrate output shocks based on actual changes in GDP in this period. The focus on backward and forward linkages provides new insight into the transmission channels for focused demand shocks at the border into more diffuse shocks within the broader Austrian economy. While the drop in global demand during the recent recession was focused on sectors producing heavy investment goods, the actual pressure this placed on the Austrian economy also hinged on the linkages of these sectors to other elements of the Austrian economy.
Keywords: F14; F44; F47; C68; 330; economic crisis; transmission mechanisms; Austria; Europe; CGE